Creating an Effective Healthcare System through Lightweight Blockchain Infrastructure and Advanced Deep Learning Techniques (International Journal of Food and Nutritional Sciences, 2021)
A radio communication sensor system comprises interconnected sensor modules utilizing wireless communication. Typically battery-powered, these modules interface with a central controller referred to as the base station. These modules perform basic computations and transmit data to the base station, often leading to energy depletion in resource-limited nodes, particularly those transmitting data from distant sources. Nodes proximate to the base station assume more extensive roles, encompassing data detection and transmission from distant nodes. The Improved Fuzzy Inspired Energy Effective Protocol (IFIEEP) addresses this energy disparity by employing three node categories to allocate more energy to underperforming nodes. Node viability is assessed based on factors like remaining energy, proximity to the base station, neighbor concentration, and centrality within a cluster, albeit these factors are founded on an uncertain premise. Effective implementation necessitates adaptive clustering, designating cluster leaders for data transmission to the base station and network-wide data dissemination. Heterogeneity parameters, encompassing node count and initial energy, are provided to guide the process. Smaller numbers of supernodes yield minor gains in network lifetime, while substantial gains, up to 100%, in covered area are achieved with increased supernodes.